Pembentukan akhlak pelajar menerusi aplikasi teknik-teknik penerapan nilai dalam pengajaran - Othman, Mohammad Khairi (Universiti Malaya, 2016)
Akhlaq and moral values among students intended to be produced by the national education system can be achieved through inculcation of noble values in teaching.Therefore, this article presents the findings related to the students’ perception of the techniques of inculcating noble values in teaching of Malay Language, History, English and Mathematics.This study used a quantitative descriptive survey research design.A total of 448 form four students from daily secondary national schools in Peninsular Malaysia participated in the survey with questionnaires as data collection instruments.The descriptive analysis findings revealed that the students’ perception of the techniques of inculcating noble values in general in teachers’ teaching of Malay Language, History, English and Mathematics was moderately high. This study found that the most used technique of inculcating noble values practiced for four subjects was role model; it was shown applied at moderately high level.In conclusion, this implies that in forming the character of students, teachers need to more frequently show a good example and be role models in terms of the student behavior, using examples from an individual's daily life by associating values and show examples of values that can be practiced in daily life.